NAFLD fibrosis score is correlated with PCSK9 and improves outcome prediction of PCSK9 in patients with chest pain: a cohort study - Peng, Jia; Liu, Ming-Ming; Jin, Jing-Lu; Cao, Ye-Xuan; Guo, Yuan-Lin; Wu, Na-Qiong; Zhu, Cheng-Gang; Dong, Qian; Sun, Jing; Xu, Rui-Xia; Li, Jian-Jun (Lipids in health and disease, 2022)
The risk of liver fibrosis in non-alcoholic fatty liver disease (NAFLD) can be easily evaluated by noninvasive scoring systems, of which the NAFLD fibrosis score (NFS) is the most commonly used. Proprotein convertase subtilisin/kexin type 9 (PCSK9), a new predictor of cardiovascular events, has been reported to be associated with cardiovascular outcomes and NAFLD. However, the relationship of NFS with PCSK9 and their prognostic abilities in cardiovascular risks are unknown. A total of 2008 hospitalized subjects who had chest pain without lipid-lowering therapy were consecutively included. Baseline clinical data were collected, and the NFS was calculated. The circulating PCSK9 concentration was determined by enzyme immunoassay. The major adverse cardiovascular event (MACE) occurrences were recorded in the follow-up period. Associations of PCSK9 concentration with NFS were examined. All of the participants were categorized into three groups according to NFS levels and were further stratified by PCSK9 tertiles to evaluate the MACEs. 158 (7.87%) MACEs were observed during a mean of 3.2 years of follow-up. NFS levels were independently related to higher PCSK9 levels according to multivariable linear regression analysis. Furthermore, elevated PCSK9 and NFS concentrations were respectively associated with increased MACE incidence in multivariable Cox regression models. When combining NFS status with PCSK9 tertiles as a stratifying factor, patients with intermediate-high NFS and high PCSK9 levels had higher risks of events than those with low NFS and low PCSK9 levels. This study revealed for the first time that NFS is positively related to PCSK9 and that the combination of NFS and PCSK9 greatly increased the risk of MACEs in patients with chest pain, providing a potential link between NFS and PCSK9 for predicting cardiovascular events.